2021
DOI: 10.1080/13102818.2021.1974945
|View full text |Cite
|
Sign up to set email alerts
|

Is gastric intestinal metaplasia a risk factor for colorectal neoplasms?

Abstract: Colorectal cancers are one of the most common types of cancer. Gastric intestinal metaplasia is considered a precancerous lesion that can progress into gastric cancer. Even though there are previous reports that Helicobacter pylori and intestinal metaplasia are related to colorectal adenomas, there are also studies stating the opposite. This study aimed explored the relationship between gastric intestinal metaplasia and colorectal neoplasia. A total of 214 patients between the ages of 19 and 92 who underwent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…[23–26] An association in each of the sequential steps of gastric cancer with colorectal neoplasms has been reported. [11] Bestas et al [27] reported that gastric intestinal metaplasia is associated with colorectal neoplasms (39.7% vs 25.3%, P = .03). Several studies reported that atrophic and metaplastic changes in the gastric corpus are associated with the development of gastric adenoma or gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[23–26] An association in each of the sequential steps of gastric cancer with colorectal neoplasms has been reported. [11] Bestas et al [27] reported that gastric intestinal metaplasia is associated with colorectal neoplasms (39.7% vs 25.3%, P = .03). Several studies reported that atrophic and metaplastic changes in the gastric corpus are associated with the development of gastric adenoma or gastric cancer.…”
Section: Discussionmentioning
confidence: 99%